2010
DOI: 10.5194/os-6-211-2010
|View full text |Cite
|
Sign up to set email alerts
|

Variability of scaling time series in the Arctic sea-ice drift dynamics

Abstract: Abstract. The motion of an individual ice floe in the ArcticOcean was monitored at the Russian research station North Pole 35 established on the ice pack in 2008. The ice floe speed (V ) was found to be correlated with wind speed (v) in main features, such as the positions of maxima and minima of V and v. However, the fine structure of the V -variation cannot be explained by the wind forcing alone. There were periods of time when the floe drift was affected by the interactions of ice floes between each other o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…On 5-8 March 2008, a strong mechanical perturbation in the Arctic ice pack occurred at a distance of ∼200 km from the Russian ice research camp North Pole 35 that drifted on the pack. A corresponding dramatic change in the speed and general direction of sea ice drift was detected at the research camp (figure 1) [22]. After the perturbation, a 'fault' consisting of fragmented sea ice was imaged by the NOAA satellite (figure 2).…”
Section: Experimental Details 21 Energy Releasementioning
confidence: 95%
“…On 5-8 March 2008, a strong mechanical perturbation in the Arctic ice pack occurred at a distance of ∼200 km from the Russian ice research camp North Pole 35 that drifted on the pack. A corresponding dramatic change in the speed and general direction of sea ice drift was detected at the research camp (figure 1) [22]. After the perturbation, a 'fault' consisting of fragmented sea ice was imaged by the NOAA satellite (figure 2).…”
Section: Experimental Details 21 Energy Releasementioning
confidence: 95%
“…e changes in the ice �oe speed were measured in 10 minutes intervals. e measurement procedure and the accuracy of the determination of changes in the value of the ice �oe speed using GPS transducer are given in [15]. A time series of kinetic energy changes (proportional to the measured Δ 2 values) in the time period of dri from 1 February to 26 February 2004 is depicted in Figure 4(a).…”
Section: Energy Exchangementioning
confidence: 99%
“…A detailed analysis of the accuracy of drift speed determination from the GPS data [4] showed that the standard error in values V measured in 2 min sampling intervals was about 0.009 m/s, while the changes in the drift speed, ΔV , were much larger. Only the values ΔV that exceeded the standard error of speed determination two times or more were taken into account in the subsequent data processing.…”
Section: Kinetic Energy Nonuniform Sea Ice Drift In the Arcticmentioning
confidence: 99%
“…The Arctic sea ice cover (ASIC) is the open thermodynamic system that exhibits well-pronounced scaling properties [1][2][3][4][5]. The ASIC dynamics is determined by the sea ice drift, which is caused, predominantly, by irregular wind forcing [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation